IMPLEMENTATION OF THE INTERNAL QUALITY ASSURANCE SYSTEM (SPMI) AS AN EFFORT TO IMPROVE THE QUALITY OF HIGHER EDUCATION IN INDONESIA - Moh Ali Fauzi; Nur Alim; Roni Harsoyo (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2024)
This study aims to describe the implementation of the Internal Quality Assurance System (SPMI) as an effort to improve the quality of education at the Kediri State Islamic Institute (IAIN). It is a qualitative research study conducted using the case study method. The research took place at the State Islamic Institute (IAIN) Kediri, with the Quality Assurance Institute (LPM) IAIN Kediri serving as the subject. The data collection techniques employed were direct observation, document and archive searches, and interviews. The results revealed the following: The policies and concepts of IQAS, in the form of academic and quality documents, were compiled by LPM IAIN Kediri. LPM IAIN Kediri coordinated the planning and implementation of SPMI across all units and faculties. The implementation of SPMI involved preparing a design in the form of an SPMI Cycle. The study identified several constraints, including limited leadership time, suboptimal human resources within LPM, and data synchronization that did not align with the Central Template. To address these constraints, steps were taken, such as training auditors and fostering a spirit of quality assurance. An evaluation of SPMI implementation was conducted annually. The utilization of SPMI implementation results included internal benefits such as fostering a culture of quality and achieving strategic plan fulfillment, as well as external benefits in terms of BAN-PT/LAM accreditation.